2020
DOI: 10.1155/2020/6148286
|View full text |Cite
|
Sign up to set email alerts
|

A Morphological and Immunohistochemical Study of the Tumoral and Inflammatory Cells in Pancreatic Ductal Adenocarcinoma

Abstract: This study is aimed at investigating tumoral and inflammatory cells and the significance of the prognostic factors of pancreatic ductal adenocarcinoma (PDAC); it is also aimed at determining the role of immunohistochemistry in the diagnosis and prognosis of this neoplasm. Materials and Methods. 230 cases of pancreatic ductal adenocarcinoma were included in the study group; these cases were selected from the archives of the Department of Pathology of the Fundeni Clinical Institute over a ten-year period. Immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…13 The authors concluded that this positivity had no relevance to the outcomes, but should be considered as a lack of absolute specificity of GATA3+ for the mammary cancers 13 . In our case, due to the age of the patient and the high titer of the CA 19-9 determination (twenty times higher than the upper normal limit), the first diagnostic concern focused a primary ductal pancreatic adenocarcinoma and local lymph nodes involvement 2,16,17 . However, the concomitant cholestasis can contribute to very elevated levels of CA19-9 and this phenomenon is described also in benign obstructions of pancreatitis, cholangitis, or cirrhosis, and levels over 1,000 U/ml may normalize with the obstruction treatment 18 .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…13 The authors concluded that this positivity had no relevance to the outcomes, but should be considered as a lack of absolute specificity of GATA3+ for the mammary cancers 13 . In our case, due to the age of the patient and the high titer of the CA 19-9 determination (twenty times higher than the upper normal limit), the first diagnostic concern focused a primary ductal pancreatic adenocarcinoma and local lymph nodes involvement 2,16,17 . However, the concomitant cholestasis can contribute to very elevated levels of CA19-9 and this phenomenon is described also in benign obstructions of pancreatitis, cholangitis, or cirrhosis, and levels over 1,000 U/ml may normalize with the obstruction treatment 18 .…”
Section: Discussionmentioning
confidence: 85%
“…Immunohistochemistry evaluation of the tumor samples in our case showed GATA3+, p63+, CK7+, Ki-67+ (50%), PR+ (10%), ER+ (5%), and HER2-, CK20-, and CDX2-. Worthy of note, a similar evaluation of pancreatic carcinomas, greater than 5 cm, in the head of the organ, frequently reveal p21-, p53+, and Ki 67+ (30-35%) in the tumor cells 17 . It is expected that an aggressive pancreatic adenocarcinoma present metastases in over than 50% of cases at the time of diagnosis 13 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation